(untitled) (Geographical Journal of Nepal, 2009)
Nepal has human settlements in high altitude areas above 3 000 masl. Those areas of Himalayan region have extreme cold climate, rugged terrains, fragile geology and slow growing vegetation, which all create very low carrying capacity for human life. Despite these, the ethnic groups have been living in those areas for several hundred years. Yet, information on those settlements in Nepal is extremely lacking and therefore, our knowledge of understanding of planning and development needs of those areas is very poor. This paper is an attempt to identify the human settlements lying above 3 000 m and analyse their distribution and size. Topographic maps of 1:50 000 have been used to find out location and size of those settlements. GIS and other software were used to extract and process required information. There are 1,282 high altitude settlements in Nepal with estimated households and population of 9,827 and 51,486 respectively. This paper analyses those settlements by altitudinal zones, major river basins from west to east, and size. The results would be helpful for further planning and development of those settlements with respect to the locally available natural resources. The Geographical Journal of Nepal, Vol. 7, 2009: 1-6